The Resepsi Nilai Hadis Birru Al-Walidain Dalam Tradisi Sadranan Di Desa Gunung Gebang: (Kajian Living Hadis) - Ilham, Ilham Syamsul; Farida, Farida Nur Anisa (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2024)
This paper wants to examine the reception of the birru al-walidain hadith in the sadranan tradition in the village of Gunung Gebang, Sleman Regency. The sadranan tradition is one of the local Islamic wisdoms carried out to welcome the holy month of Ramadan. This research departs from the assumption that the implementation of the sadranan tradition is based on the birru al-walidain hadith. The research method used is a type of qualitative research based on field studies. Data collection was carried out through interviews, apart from that, data was also taken from several literatures that have correlations. This research aims to answer three questions, namely 1) How is the sadranan tradition implemented in Gunung Gebang Village, Prambanan District, Sleman Regency? 2) What is the community's view of the sadranan tradition? 3) How is the hadith reception regarding the sadranan tradition? The results of this research are that the sadranan tradition in Gunung Gebang Village has positive values ​​in the view of its people. Explicitly, this tradition is not based on hadith evidence, but implicitly this tradition is in line with the values ​​of the birru al-walidain hadith.